2015
DOI: 10.1021/jp5093543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alumina Thickness on CO Oxidation Activity over Pd20/Alumina/Re(0001): Correlated Effects of Alumina Electronic Properties and Pd20Geometry on Activity

Abstract: The CO oxidation activity of size-selected Pd 20 clusters deposited on alumina films grown on Re(0001) is shown to depend strongly on the film thickness in the 0 to 10 nm range. For the reaction conditions of these experiments, binding and activation of O 2 is shown to be the limiting process, which can be varied by a factor of 2 by tuning the alumina film thickness, due to effects on both the electronic structure of the alumina film and the morphology of the supported Pd clusters. The alumina films are shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 109 publications
1
29
0
Order By: Relevance
“…Similar concepts also apply to molecules adsorbed on insulating ultrathin films: The gap between the highest occupied and lowest unoccupied molecular orbital as well as the charge transfer upon adsorption depend not only on polarization effects at the interface, but to a large extent also on the thickness of the insulating layer [9][10][11]. Catalytic activity can also change drastically in such systems: Recently, it was shown that due to changes in the electronic properties, the CO oxidation activity of palladium clusters deposited on alumina (Al 2 O 3 ) films on Re(0001) strongly depends on the film thickness [12]. To fully understand which properties of the adsorbed species rely on the adsorbate/oxide interface and which are influenced by the underlying substrate material, the oxide thickness needs to be varied in a controlled manner [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similar concepts also apply to molecules adsorbed on insulating ultrathin films: The gap between the highest occupied and lowest unoccupied molecular orbital as well as the charge transfer upon adsorption depend not only on polarization effects at the interface, but to a large extent also on the thickness of the insulating layer [9][10][11]. Catalytic activity can also change drastically in such systems: Recently, it was shown that due to changes in the electronic properties, the CO oxidation activity of palladium clusters deposited on alumina (Al 2 O 3 ) films on Re(0001) strongly depends on the film thickness [12]. To fully understand which properties of the adsorbed species rely on the adsorbate/oxide interface and which are influenced by the underlying substrate material, the oxide thickness needs to be varied in a controlled manner [13].…”
Section: Introductionmentioning
confidence: 99%
“…Model catalysis on supported transition-metal particles under ultrahigh-vacuum (UHV) conditions allows precise control of critical factors that govern heterogeneously catalyzed reactions,t hereby reducing the complexity of the system and allowing targeted investigations of key parameters influencing the reaction activity,selectivity,and specificity of acatalyst. [1][2][3] To date,UHV studies have shown the ability to influence the chemical and/or morphological properties of nanoparticles supported on thin metal oxide films [4] by controlling the precise particle size, [5][6][7][8][9] the film thickness, [10][11][12][13][14][15] the presence of defect sites, [4,6,16] and the reduction state of the thin film. [17] Acommonly used support in heterogeneous catalysis is a-SiO 2 , [18,19] and it has been shown that a-SiO 2 thin films grown in UHV provide an opportunity to vary the metal oxide stoichiometry through selection of the growth parameters.…”
mentioning
confidence: 99%
“…5a, no 13 with Pt in this temperature range. On the other hand, we have also observed CO desorption in this temperature range for defective alumina films grown on single crystal supports, [42,45,46] thus the sites exposed by annealing may simply be defects in the alumina.…”
Section: Co Desorption As a Probe Of Pt Binding Sitesmentioning
confidence: 60%